MANIFESTATIONS OF THE CONFLICT BETWEEN THE MONK COMMUNITY OF THE HLYNSKA HERMITAGE WITH THE SOVIET AUTHORITY AT THE END OF THE 1950s – THE BEGINNING OF THE 1960s. - OLITSKYI, Viacheslav (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the article is to clarify the causes and nature of the conflict between the monastic community of the Hlynska Hermitage and the Soviet authorities at the end of the 1950s and the beginning of the 1960s, to study the forms of resistance of the monastic community and the reaction to them by state authorities, and to determine the consequences of this confrontation. The research methodology is based on the principles of objectivity and systematicity. To achieve the goal and objectives, general scientific methods have been used – analysis, synthesis, generalization, induction, deduction, as well as special methods of historical research – classification and criticism of sources, problem-chronological, comparative historical. The scientific novelty consists in the fact that for the first time, the manifestations of the conflict between the monastic community of the Hlynska Hermitage and the Soviet authorities on the eve of the monastery's closure have become the object of a separate scientific study. Conclusions. The monastic community of the Hlynska Hermitage used passive and active forms of resistance. Passive forms include assistance to pilgrims, provision of food, lodging, and failure to take measures recommended by the authorities to stop such assistance. A form of active resistance was the sabotage of Soviet elections, the refusal of individual monks to commemorate the Soviet regime during church services. This was prompted by an internal ethical and spiritual call, since praying for a godless regime that actively destroyed the Church and closed monasteries and temples seemed contradictory. The monks' resistance was spontaneous and unorganized, but in terms of ideological significance it was of serious importance to the authorities. The authorities actively responded to any attempts by the monastic community to resist the established order, using various means of influence – from formal control to pressure and direct persecution of dissenting monks. The confrontation between the monastic community of the Hlynska Hermitage and the Soviet authorities had significant consequences for the monastic community, as a significant part of the monks were expelled, and the monastery itself was under constant surveillance. Keywords: Orthodox Church, monastery, monks, clergy, Soviet government, repressions, Sumy region.